TRPV2: A Cancer Biomarker and Potential Therapeutic Target - Siveen, Kodappully S.; Nizamuddin, Parveen B.; Uddin, Shahab; Al-Thani, Mohamed; Frenneaux, Michael Paul; Janahi, Ibrahim A.; Steinhoff, Martin; Azizi, Fouad (Disease Markers, 2020)
The Transient Receptor Potential Vanilloid type-2 (TRPV2) channel exhibits oncogenicity in different types of cancers. TRPV2 is implicated in signaling pathways that mediate cell survival, proliferation, and metastasis. In leukemia and bladder cancer, the oncogenic activity of TRPV2 was linked to alteration of its expression profile. In multiple myeloma patients, TRPV2 overexpression correlated with bone tissue damage and poor prognosis. In prostate cancer, TRPV2 overexpression was associated with the castration-resistant phenotype and metastasis. Loss or inactivation of TRPV2 promoted glioblastoma cell proliferation and increased resistance to CD95-induced apoptotic cell death. TRPV2 overexpression was associated with high relapse-free survival in triple-negative breast cancer, whereas the opposite was found in patients with esophageal squamous cell carcinoma or gastric cancer. Another link was found between TRPV2 expression and either drug-induced cytotoxicity or stemness of liver cancer. Overall, these findings validate TRPV2 as a prime candidate for cancer biomarker and future therapeutic target.